Impact Of the Deleterious Effects of Academic Stress on University Athletes’ Sports Performance Outcomes - Javeed, Qamar; Tabassum, Yasmeen; Javeed, Samna (ACADEMIA International Journal for Social Sciences, 2025)
This study investigates the impact of the deleterious effects of academic stress on university student-athletes’ sports performance outcomes in Pakistan, using a cross-sectional survey design. Data were collected from 264 undergraduate and postgraduate athletes actively competing at various levels. Standardized instruments, including the Perceived Stress Scale (PSS-10), Academic Stress Scale, and Athlete’s Subjective Performance Scale (ASPS), measured general stress, academic stress, and self-perceived sports performance, respectively. Descriptive statistics, reliability testing (Cronbach’s alpha ≥ 0.75), correlational analysis, and multiple linear regression were conducted using IBM SPSS Statistics (Version 26). The study highlights the role of psychological capital and institutional support, such as flexible schedules and mental health resources, in mitigating stress.Findings suggest universities should implement targeted interventions, including time management training and counseling, to support student-athletes’ academic and athletic success.